2021
DOI: 10.1021/acs.biomac.1c01087
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Green Fluorescent Cross-Linked Poly(ester amide)s by Spontaneous Zwitterionic Copolymerization

Abstract: The spontaneous zwitterionic copolymerization (SZWIP) of 2-oxazolines and acrylic acid affords biocompatible but low molecular weight linear N-acylated poly­(amino ester)­s (NPAEs). Here, we present a facile one-step approach to prepare functional higher molar mass cross-linked NPAEs using 2,2′-bis­(2-oxazoline)­s (BOx). In the absence of solvent, insoluble free-standing gels were formed from BOx with different length n-alkyl bridging units, which when butylene-bridged BOx was used possessed an inherent green … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It has been reported that the different pH conditions have obvious effects on the probe molecules with acidic/basic moieties. 38 For PIE-active PAMs, morpholine and amide moieties along the macromolecular chains endow PAMs with alkalinity, and the changes in pH cause different physical properties. To investigate the effect of pH on the fluorescence of PAM-TB solution, we measured the fluorescence spectra of PAM-TB at different pH values (pH = 0–12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the different pH conditions have obvious effects on the probe molecules with acidic/basic moieties. 38 For PIE-active PAMs, morpholine and amide moieties along the macromolecular chains endow PAMs with alkalinity, and the changes in pH cause different physical properties. To investigate the effect of pH on the fluorescence of PAM-TB solution, we measured the fluorescence spectra of PAM-TB at different pH values (pH = 0–12).…”
Section: Resultsmentioning
confidence: 99%
“…44 Compared with AIE-active small molecules, the PIE-active polymer generally has outstanding photostability or bleach resistance in biological imaging. 38 In our investigation, the light stability of both PAM-TM and LysoTracker Red was tested by continuous laser scanning confocal microscopy. It was found that PAM-TM lost only about 20% of its signal over 9 min (see Fig.…”
Section: Target Imaging Of Pam-tm For Lysosomes and Tracking Fe 3+ Ionsmentioning
confidence: 99%
“…[ 17 ] In the present study, bis(2‐butyl‐2‐oxazoline) (BBOx) was selected as crosslinker due to its good water‐solubility. [ 39 ] The target DP of PMeOx was increased to 100 concomitant with an increase of the reaction time to 24 h. 5 and 10 mol.% of BBOx yielded crosslinked PMeOx as demonstrated by the inversion test. Similarly, RAFT polymerization of DMAAm using 10 mol.% of BAM gave the respective PDMAAm hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…1,4‐Butylene‐2,2‐bis(2‐oxazoline) (BBOx) was prepared by a modified literature procedure. [ 39 ] Chain transfer agent (CTA) (2‐cyanobutanyl‐2‐yl 3,5‐dimethyl‐1H‐pyrazole‐1‐carbodithioate) (CDPC) was obtained from Boron Molecular (Noble Park, Victoria). Deuterated chloroform (CDCl3, 99.8%) was purchased from Cambridge Isotope Labs.…”
Section: Methodsmentioning
confidence: 99%
“…Glycol chitosan (GC) and its derivatives are extensively studied as carriers due to ease in functionalization that imparts properties of biocompatibility, mucoadhesion, and ease of modification in biodistribution due to the availability of functional groups [18][19][20][21][22]. Chang-Moon Lee et al have shown that the hydrophobic modification of the chitosan with linoleic acid can be exploited to increase the hepatocyte-specific uptake of chitosancoated superparamagnetic iron oxide nanocrystals.…”
Section: Introductionmentioning
confidence: 99%